Discourses of service recipients in the context of reablement in Norway. (3rd April 2021) - Ranner, Maria; Vik, Kjersti
Abstract: Background: Reablement is a shift from reactive home care to a more preventive model based on active engagement. In this shift, it is interesting to uncover and understand potential discourses that may exist amongst service providers regarding their views of service recipients. Aim: to explore and describe discourses of the view of service recipients in the context of reablement, from the service providers' perspective. Method: Participants were service providers working in reablement, with the analysis being retrieved from 13 focus groups. A critical discourse analysis was used in order to gain a broader understanding and to capture service providers' views. Findings: Five discourses were constructed. Three discourses indicated the way participants perceived service recipients included in reablement, namely the competent service recipient, the conventional service recipient, and the perfect service recipient. Two discourses categorised recipients related to whether or not they were included in reablement: the suitable service recipient who was excluded and the unsuitable service recipient who was included . Conclusion: Service providers use a variety of different discourses when they talk about service recipients. Significance: Service providers, including occupational therapists, must be aware of how unconscious discourses can affect those to whom they provide services.